Developing a situation analysis tool to assess containment of antimicrobial resistance in South East Asia. (5th September 2017) - Kakkar, Manish; Sharma, Anuj; Vong, Sirenda
Abstract : Manish Kakkar and colleagues discuss the development of a tool to assess how programmes tackling antimicrobial resistance in South East Asia are faring